An Analysis of Social Class and Discrimination in All Day and A Night Movie - Anggraini, Loisti; Rullyanti, Merry; Pradana, Ami (Jurnal Penelitian Multidisiplin Bangsa, 2026)
This study discusses social class and discrimination in the film All Day And A Night. This study has two objectives. (1) To identify forms of social class and discrimination in the film All Day And A Night (2) To investigate the factors that cause social class and discrimination in the film All Day And A Night. This study uses a descriptive qualitative method. This relates to the description of data in the form of dialogue or conversation as well as descriptive actions that occur in the film. In this study, the researcher used Karl Marx and Sorokin's theories to analyze social class and theories from the U.S. Equal Employment Opportunity Commission and Newman for discrimination. The findings of this study show that there are 11 forms of social class, 6 from the bourgeoisie and 5 from the proletariat, as well as 9 factor from wealth, income, and influence and 3 from occupation, and. Furthermore, 9 data were found for discrimination: 5 from harassment and 4 from race/color discrimination, as well as 2 factors from verbal discrimination, 1 from Avoidance, and finally 6 from physical discrimination. Thus, based on this data, the researcher found 11 data for social class and 9 data for discrimination in the film All Day And A Night.